Change of Endoglucanase Activity and Rumen Microbial Community During Biodegradation of Cellulose Using Rumen Microbiota - Takizawa, Shuhei; Asano, Ryoki; Fukuda, Yasuhiro; Feng, Mengjia; Baba, Yasunori; Abe, Kenichi; Tada, Chika; Nakai, Yutaka (Frontiers in Microbiology, 2020)
Treatment with rumen microorganisms improves the methane fermentation of undegradable lignocellulosic biomass; however, the role of endoglucanase in lignocellulose digestion remains unclear. This study was conducted to investigate endoglucanases contributing to cellulose degradation during treatment with rumen microorganisms, using carboxymethyl cellulose (CMC) as a substrate. The rate of CMC degradation increased for the first 24 h of treatment. Zymogram analysis revealed that endoglucanases of 52 and 53 kDa exhibited high enzyme activity for the first 12 h, whereas endoglucanases of 42, 50, and 101 kDa exhibited high enzyme activities from 12 to 24 h. This indicates that the activities of these five endoglucanases shifted and contributed to efficient CMC degradation. Metagenomic analysis revealed that the relative abundances of Selenomonas, Eudiplodinium, and Metadinium decreased after 12 h, which was positively correlated with the 52- and 53-kDa endoglucanases. Additionally, the relative abundances of Porphyromonas, Didinium, unclassified Bacteroidetes, Clostridiales family Ⅺ, Lachnospiraceae, and Sphingobacteriaceae increased for the first 24 h, which was positively correlated with endoglucanases of 42, 50, and 101 kDa. This study suggests that uncharacterized and non-dominant microorganisms produce and/or contribute to activity of 40, 50, 52, 53, and 101 kDa endoglucanases, enhancing CMC degradation during treatment with rumen microorganisms.